Catalytic Asymmetric Syntheses of 3-Monosubstituted Oxindoles - Liu, Xigong; Liu, Lei (Synthesis, 2024)
Chiral 3-monosubstituted oxindoles are privileged structural motifs in a variety of natural products and synthetic pharmaceuticals. However, catalytic asymmetric syntheses of these structural motifs remain challenging, mainly because of the ease of racemization of the tertiary stereocenter through enolization. In this short review, asymmetric synthetic methods for the preparation of chiral 3-monosubstituted oxindoles are summarized from the perspective of four different strategies, including Michael addition, carbenoid-mediated C–H insertion, decarboxylative protonation, and indole oxidation.1 Introduction2 Asymmetric Michael Addition3 Asymmetric Carbenoid-Mediated C–H Insertion4 Asymmetric Decarboxylative Protonation5 Asymmetric Indole Oxidation6 Others7 Conclusion
Keywords: 3-monosubstituted oxindole; asymmetric catalysis; asymmetric synthesis; synthetic method; bioactive molecules